INOVASI MODEL BISNIS BANK MUAMALAT INDONESIA - M. Ruslianor Maika (Universitas Muhammadiyah Sidoarjo, 2016)
Business model innovators (BMI) earned an average premium that was more than four times greater than that enjoyed by product or process innovators. Furthermore, BMI delivered returns that were more sustainable; even after ten years, business model innovators continued to outperform competitors and product and process innovators (BCG, 2009). Innovation is done using a device management such as: Business Model Canvas (BMC) and the design thinking approach (DTA). BMC used to mapping the Bank Muamalat through the 9 building blocks for later in-design a new business model to conduct the interview process to collect ideas and find an innovative solution.